Программа самовдосконалення суб’єктів освітнього процесу - Ігнатюк, Ольга Анатоліївна; Перехрест, Н. В. (НТУ "ХПІ", 2016)
Статтю присвячено проблемі забезпечення процесу саморозвитку та самовдосконалення суб’єктів освітнього процесу у вищих навчальних закладах. Розкриваються особливості співвідношення самоприняття і прагнення до самовдосконалення у суб’єктів освітнього процесу вузу, їх вплив на спрямованість навчальної мотивації студентів. У полі зору перебувають питання самоосвіти, особистісного росту, професіоналізму.

The article is devoted to the problem of ensuring the process of self-development and self-improvement subjects of the educational process in higher educational institutions. The peculiarities of correlation of self-acceptance and striving for self-improvement among the subjects of the educational process of the University, their influence on the direction of educational motivation of students. In field of view are questions of self-education, of personal increase and professionalism.
The program of self-improvement subjects of the education process
Keywords: мотивація; спрямованість навчальної мотивації; самоприняття; самоосвіта; особистісний ріст; професіоналізм; motivation; self-acceptance; self-education; personal growth